2020
DOI: 10.4149/gpb_2019061
|View full text |Cite
|
Sign up to set email alerts
|

AZGP1 suppresses the process of colorectal cancer after upregulating FASN expression via mTOR signal pathway

Abstract: Colorectal cancer (CRC) is the most common malignant gastrointestinal tumor. Obesity has been confirmed to be closely related to the occurrence of CRC, but the specific mechanism is not clear. This study mainly explored the roles of obesity-related genes, fatty acid synthase (FASN) and zinc-alpha-2-glycoprotein (AZGP1) in CRC. 30 cases of CRC tissues and adjacent normal colorectal tissues were obtained to quantify the levels of FASN and AZGP1 using qRT-PCR and Western blotting. Overexpression-AZGP1, overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“… 45 However, another team observed that AZGP1 was highly expressed in colorectal cancer tissue with liver metastasis and associated with unfavorable survival, and that AZGP1 facilitates metastasis by regulating the epithelial-mesenchymal transition. 46 In our study, the expression of AZGP1 was upregulated both in HCT-116-R and CX-1-R cells, suggesting its participation in the acquisition of radioresistance. Subsequently, the microarray data from GEO validated the upregulation of AZGP1 in both radioresistant cells and tissues.…”
Section: Discussionsupporting
confidence: 52%
“… 45 However, another team observed that AZGP1 was highly expressed in colorectal cancer tissue with liver metastasis and associated with unfavorable survival, and that AZGP1 facilitates metastasis by regulating the epithelial-mesenchymal transition. 46 In our study, the expression of AZGP1 was upregulated both in HCT-116-R and CX-1-R cells, suggesting its participation in the acquisition of radioresistance. Subsequently, the microarray data from GEO validated the upregulation of AZGP1 in both radioresistant cells and tissues.…”
Section: Discussionsupporting
confidence: 52%
“…The down-regulation of HAGH expression has been shown to have significant antiproliferative effects on colorectal cancer [37]. AZGP1 has been reported to inhibit colorectal cancer progression via the mTOR signaling pathway and has also been shown to suppress the progression of malignant soft-tissue sarcoma cells [38]. LDHD has been reported to be a regulator of energy metabolism and is involved with tumor cell glycolysis within the tumor microenvironment [39].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of AZGP1 can activate the PTEN/Akt and CD44 pathways, thereby promoting metastasis and migration, and it is associated with poor prognosis 19 . Furthermore, AZGP1 overexpression suppresses invasion and cell proliferation by inhibiting MMP‐2 and MMP‐9 expression, and it inhibits the activation of mTOR pathway 38 . Accordingly, loss of AZGP1 promotes EMT, accompanied by increased invasion, decreased apoptosis and proliferation, pro‐survival signals and a shift in energy metabolism 13,20 .…”
Section: Discussionmentioning
confidence: 99%